Mexicans and Mexican Americans in Michigan - Alvarado, Rudolph (Book collections on Project MUSE., 2003)
Unlike most of their immigrant counterparts, up until the turn of the twentieth century most Mexicans and Mexican Americans did not settle permanently in Michigan but were seasonal laborers, returning to homes in the southwestern United States or Mexico in the winter. Nevertheless, during the past century the number of Mexicans and Mexican Americans settling in Michigan has increased dramatically, and today Michigan is undergoing its third "great wave" of Mexican immigration. Though many Mexican and Mexican American immigrants still come to Michigan seeking work on farms, many other.